Exploring the E-Commerce Corn Dog: an MBKM Program by UIGM Students to Support MSMEs - Apriyanti, Apriyanti; Hertati, Lesi; Asharie, Asmawati; Avini, Terti (CV. Proaksara Global Transeduka, 2023)
In facing the ever-growing digital era, Indo Global Mandiri University (UIGM) students, as agents of change, are expected to be able to utilize e-commerce to support the Student-Based Internship Program (MBKM) with a focus on Micro, Small, and Medium Enterprises (MSMEs). This activity, entitled